Crystal method. - Stevenson, R. (IEEE spectrum)
The author discusses a potential method for commercial production of GaN substrates, developed by a UK company, NanoGaN. Their nanocolumn growth technique is used to grow high-quality nanosized gallium nitride wafers on sapphire substrate. This method is based on the vapour deposition of GaN thin film on substrate, forming an array of nanometer-size holes in the surface of gallium, then producing gallium nitride layer by layer. The described approach can produce high quality GaN crystals with very few defects.